2019
DOI: 10.1016/j.celrep.2019.04.110
|View full text |Cite
|
Sign up to set email alerts
|

Sterile Lung Inflammation Induced by Silica Exacerbates Mycobacterium tuberculosis Infection via STING-Dependent Type 2 Immunity

Abstract: Graphical Abstract Highlights d Silica impairs host control of M. tuberculosis infection via a type 2 immune response d Extracellular DNA potentiates silica-induced exacerbation of M. tuberculosis infection d Silica primes STING activation, potentiating the response to M. tuberculosis DNA d Both host and M. tuberculosis DNA trigger cGAS/STING/ IFNI-mediated type 2 immunity SUMMARY Lung inflammation induced by silica impairs host control of tuberculosis, yet the underlying mechanism remains unclear. Here, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 53 publications
(63 reference statements)
2
40
0
Order By: Relevance
“…We found that microglia were significantly activated and polarized into M1 phenotype after SAH, as evidenced by the morphological changes and increased level of microglial M1 markers CD16, IL-1β, iNOS, IL-6, TNF-α, and NLRP3 inflammasome. Similar to previous literature demonstrating the effect of STING in modulating macrophage polarization [49,50], our data indicated that activation of STING could enhance inflammatory response through promoting microglial activation and polarizing into pro-inflammatory M1 phenotype. And treatment with C-176 significantly inhibited STING-mediated neuroinflammation after SAH.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that microglia were significantly activated and polarized into M1 phenotype after SAH, as evidenced by the morphological changes and increased level of microglial M1 markers CD16, IL-1β, iNOS, IL-6, TNF-α, and NLRP3 inflammasome. Similar to previous literature demonstrating the effect of STING in modulating macrophage polarization [49,50], our data indicated that activation of STING could enhance inflammatory response through promoting microglial activation and polarizing into pro-inflammatory M1 phenotype. And treatment with C-176 significantly inhibited STING-mediated neuroinflammation after SAH.…”
Section: Discussionsupporting
confidence: 90%
“…Meanwhile, the M2 phenotype microglia were identified to release anti-inflammatory and neuroprotective effects via secreting anti-inflammatory cytokines and promoting neural regeneration, oligodendrogenesis, and angiogenesis [48]. Notably, recent studies demonstrated that activation of STING could repolarize macrophages from M2 phenotype into M1 phenotype in a disease model of tuberculosis infection and colitis [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Mtb infects via inhalation of a low dose of aerosolized bacteria; therefore, low-dose aerosol inoculation would better mimic the nature of Mtb infection in humans. However, in the absence of the ability to perform aerosolized infections, the standard experimental protocol of Mtb infection in mice is 1,000 CFU via intranasal inoculation (69)(70)(71)(72). Monocytes play an essential role in initiating T-cell responses in the lung against Mtb infection (73), and using this standard protocol of Mtb infection in mice, we previously observed monocytosis (64), similar to what has been reported in other studies using aerosolized low-dose infection protocols (74,75).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, host control of mycobacterial infection relies on type 1 immunity. However, we found that silica pre‐exposure activates the DNA/cGAS/STING pathway and increases the type 1 IFN response to mycobacterial infection that, in turn, enhances type 2 immunity and favours infection in mice 3 …”
Section: Figurementioning
confidence: 73%